Servqual-Based Service Quality Optimization to Drive Profit Growth at ITTR English Course - Shelby Riani Altinia; Akbar Adhi Utama (Green Publisher Indonesia, 2026)
A long standing English language school in Indonesia called ITTR English Course has seen flat profits even though student numbers have remained steady, which suggests there are deep problems with the quality of its services. The goal of this research is to assess current service standards and develop strategic improvements that will boost student satisfaction, increase retention, and lift the institution's financial performance. Using a sequential explanatory mixed-methods approach, this research combined quantitative SERVQUAL surveys analyzed through Structural Equation Modeling (SEM) with qualitative NVivo analysis to pinpoint service issues. Problems were diagnosed using Fishbone and Current Reality Tree (CRT) methods, ranked through Analytic Hierarchy Process (AHP), and addressed by developing action strategies with the House of Quality (HOQ) and the Plan–Do–Check–Act (PDCA) framework. Based on the study, student satisfaction is most heavily influenced by the reliability and assurance aspects of service quality. Satisfied students then become loyal customers, which directly supports the institution's bottom line. The author recommends focusing on teacher training, classroom facilities, and communication speed, alongside implementing scheduled feedback systems. In conclusion, managing service quality effectively is demonstrated to be the best way to secure ongoing student fulfillment, retention, and profitability.